The dance of freedom : Texas African Americans during Reconstruction - Crouch, Barry A., 1941- (Jack and Doris Smothers series in Texas history, life, and culture ;, 2007)
This anthology brings together the late Barry A. Crouch's most important articles on the African American experience in Texas during Reconstruction. Grouped topically, the essays explore what freedom meant to the newly emancipated, how white Texans reacted to the freed slaves, and how Freedmen's Bureau agents and African American politicians worked to improve the lot of ordinary African American Texans. The volume also contains Crouch's seminal review of Reconstruction historiography, "Unmanacling Texas Reconstruction: A Twenty-Year Perspective." The introductory pieces by Arnoldo De Leon and Larry Madaras recapitulate Barry Crouch's scholarly career and pay tribute to his stature in the field of Reconstruction history.